2013
DOI: 10.1159/000354913
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Noise-Protective Action of the Olivocochlear Efferents in Humans

Abstract: It has been demonstrated in different mammals that the medial olivocochlear efferents (MOC) exert a noise-protective effect on the cochlea. In humans such an effect has not unambiguously been shown as of yet. The objective of this study was to assess the relationship between MOC activity and susceptibility of the cochlea to noise-induced hearing loss in humans. In 40 normally hearing human subjects, we measured the following: (1) magnitude of temporary threshold shift (TTS) after exposure to 60 min broadband n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
(38 reference statements)
1
10
0
2
Order By: Relevance
“…Recently, Wolpert et al (2014) showed that the difference in DPOAE growth functions with and without a contralateral elicitor was moderately predictive of temporary threshold shift (TTS) magnitude. Although promising, this finding might not generalize to permanent threshold shift (PTS) risk, because PTS and TTS do not have the same physiological underpinnings (e.g., Nordmann et al, 2000), and in its current form this test takes too long for a clinical assay.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wolpert et al (2014) showed that the difference in DPOAE growth functions with and without a contralateral elicitor was moderately predictive of temporary threshold shift (TTS) magnitude. Although promising, this finding might not generalize to permanent threshold shift (PTS) risk, because PTS and TTS do not have the same physiological underpinnings (e.g., Nordmann et al, 2000), and in its current form this test takes too long for a clinical assay.…”
Section: Introductionmentioning
confidence: 99%
“…Inner hair cells (IHC), the primary auditory receptor cells of the mammalian cochlea, are contacted by Type I spiral ganglion cell afferents that are themselves addressed by OC efferents. Although the function of OC neurons (OCN) is not fully understood so far, a protective role against acoustic overexposure and the discrimination of sounds from noise are discussed (Kawase et al, ; Guinan, ; Wolpert et al, ). It is agreed to that OCN may exert excitatory and inhibitory influence on OHC somata and IHC afferents (Giraud et al, ; Hill et al, ; Chen et al, , cf.…”
mentioning
confidence: 99%
“…Recently, Wolpert et al ( 2014 ) studied a group of subjects ( n = 40) who were exposed to a 60-min. broadband noise at 94 dB SPL.…”
Section: Human Studiesmentioning
confidence: 99%